A Multidisciplinary Technique Using Endonasal Endoscopic Approach with Intrathecal Fluorescin Under Neuronavigation Guidance in Patients with Cerebrospinal Fluid Leak - Seddighi, Afsoun; Nikouei, Amir; Seddighi, Amir Saied (International Clinical Neuroscience Journal, 2017)
Background: Cerebrospinal fluid (CSF) is contained in an anatomic space, including cerebral ventricles and subarachnoid spaces and cisterns of brain and spine. Distraction of normal anatomy of any containing parts of this system will result in CSF leakage which could be associated with morbidity and mortality with variable degrees. In this study, we aimed to present 3 patients with history of blunt head trauma, who presented with delayed CSF leak and underwent endonasal endoscopic approach under image guided surgery using neuronavigation system with fluorescein illumination. Case Presentation: Three patients were referred to neurosurgery department of Shohada Tajrish Hospital with previous history of blunt head trauma, complained from CSF rhinorrhea. They underwent thin slice Computed Tomography scan and received intrathecal fluorescein for better visualization of leakage source under live endonasal endoscopic approach, using image guided neuronavigation technology. Autologous fat tissue and fascia was used to seal the leakage site. Clinical and imaging follow up at post-operative state as well as 1st, 2nd, 4th and 8th week revealed no post-operative complications and repeated CSF leakage. Conclusion: CSF rhinorrhea indicates abnormality in bony structure of skull base and is a major threat for ascending microbial infections and subsequent meningitis. Thus, identification of leakage site(s) and accurate surgical repair is necessary. We experienced a multidisciplinary approach which showed excellent results and no post-operative complications. Multidisciplinary approach with combination of endonasal endoscopic view under neuronavigation system improves accuracy and will minimize post-operative complications.